An Efficient Interfacial Synthesis of Two‐Dimensional Metal–Organic Framework Nanosheets for Electrochemical Hydrogen Peroxide Production. (9th April 2021) - Wang, Mengjun; Dong, Xu; Meng, Zhaodong; Hu, Zhiwei; Lin, Yan‐Gu; Peng, Chun‐Kuo; Wang, Hongshuai; Pao, Chih‐Wen; Ding, Songyuan; Li, Youyong; Shao, Qi; Huang, Xiaoqing
Abstract: Two‐dimensional (2D) metal–organic framework nanosheets (MOF NSs) play a vital role in catalysis, but the most preparation is ultrasonication or solvothermal. Herein, a liquid–liquid interfacial synthesis method has been developed for the efficient fabrication of a series of 2D Ni MOF NSs. The active sites could be modulated by readily tuning the ratios of metal precursors and organic linkers (RM/L ). The Ni MOF NSs display highly RM/L dependent activities towards 2e oxygen reduction reaction (ORR) to hydrogen peroxide (H2 O2 ), where the Ni MOF NSs with the RM/L of 6 exhibit the optimal near‐zero overpotential, ca. 98 % H2 O2 selectivity and production rate of ca. 80 mmol gcat −1 h −1 in 0.1 M KOH. As evidenced by X‐ray absorption fine structure spectroscopy, the coordination environment of active sites changed from saturation to unsaturation, and the partially unsaturated metal atoms are crucial to create optimal sites for enhancing the electrocatalysis. Abstract : 2D Ni metal–organic framework nanosheets (MOF NSs) with controlled coordination mode were carefully created through a liquid–liquid interfacial synthesis strategy for the first time and adopted as efficient electrocatalysts for hydrogen peroxide (H2 O2 ) synthesis. The optimized partially unsaturated Ni MOF NSs‐6 exhibits near‐zero overpotential as well as ca. 98 % H2 O2 selectivity in 0.1 M KOH, exceeding most electrocatalysts up to date.